Identifikasi Keanekaragaman Hayati dan Pemetaan Bawah Tanah Kampus Terpadu Universitas Muhammadiyah Palangkaraya Sebagai Media Objek Pembelajaran - Nurul Hikmah Kartini; Indah Sari Dewi (​Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2013)
Innovative learning in addition to varied models, strategies and methods, it is also necessary to approach. The lack of understanding of the basic concepts of science underpins researchers to create learning media for the identification of biodiversity and the subsurface layer in the form of underground layers. Lack of information on previous research regarding research at UM Palangkaraya Integrated Campus on Jl. Anggrek-Mahir Mahar made researchers try to link the environmental approach of UM Integrated Campus area Learning with the final achievement in the form of science media learning objects. This research method began with an initial theoretical study of science learning, followed by a field survey. Observations in the field will examine an area of ​​1 ha identified as having higher biodiversity than others. After setting the plot point, the acquisition is carried out with 2 (two) stages, namely the identification of biodiversity with the sampling of flora and fauna that are at the plot point. The next stage is the acquisition of underground layer mapping using the Self Potential method with porous copper pot and CuSO4 solution. After the acquisition, continued data analysis of the two stages. Biodiversity in the form of flora and fauna types and layer contour maps are poured into learning object media. Hope in the future, researchers can continue mapping the surface and subsurface of the Palangkaraya UM Integrated Campus in an area of ​​20 ha.